Analisis Penerapan Good Corporate Governance (GCG) dan Pengaruhnya Terhadap Kinerja Lembaga Bank Syariah - Devi Rizki Zahrawani; Nining Sholikhah (Jurnal Ilmiah Ekonomi Islam, 2021)
The implementation of good corporate governance is the first step to improve company's performance and reputation. For Islamic People Financing Banks (BPRS), the implementation of good corporate governance can be a good magnet for consumer and is able to increase business improvement. Meanwhile, the implementation of bad corporate governance will bring BPRS in a vulnerable situation towards some problems and it has no resiliency. The low resistance of BPRS will cause a poor management of BPRS. This condition affects to financial management. This research uses descriptive qualitative method. The aim of this research is to realize the implementation of good corporate governance and its significance towards performance and financial performance of PT. Bank Pembiayaan Syariah Central Syariah Utama in Surakarta in year 2017-2019.